Studies on the primary productivity of a freshwater fishpond by the chlorophyll method. - Galsim, Juanito G. (College of Fisheries, University of the Philippines, 1969)
Variations in chlorophyll concentration obtained from existing phytoplankton population occur as a result of environmental changes. Fluctuations in sunlight intensity, temperature, and turbidity of the pond water brought about changes in the chlorophyll concentrations of the pond. High sunlight illumination brought about increases in chlorophyll concentration. The relationship between water temperature alone and chlorophyll concentration was not well established in this study. Maximum concentrations of chlorophyll obtained from Pond Nos. 5 and 6 were 0.471 gram/m3 and 0.513 gram/m3 respectively with the prevailing sunlight intensity between 250-350 gram-calorie/cm2 and an accompanying water temperature of 26°C.